Strategi Pemasaran Inklusif untuk Meningkatkan Partisipasi Dana Pensiun Pekerja Sektor Informal di Indonesia: Analisis Hambatan, Segmentasi Pasar, dan Rekomendasi Implementasi - Syarifudin Yunus; Farid Nabil Elsyarif (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2026)
This study on inclusive marketing strategies to increase participation in pension funds among informal sector workers in Indonesia was conducted using a descriptive method with a mixed-methods approach, with a sample of 100 informal workers in the Greater Jakarta area. The study concluded that barriers to pension fund/DPLK participation among informal sector workers include: the perception that pension funds are illiquid (difficult to withdraw) at 28%, lack of education at 22%, the fact that participation is not mandatory or a lack of awareness at 19%, the lack of digital access at 13%, the perception that the system is absurd at 13%, and the perception that it is only for office workers at 5%. A transformation of the pension fund/DPLK marketing strategy is needed, shifting from a product-oriented approach to a participant-centered one. Segmentation of informal workers to increase pension fund participation can be divided into 1) traditional informal groups (lower tier), such as day laborers, street vendors, domestic workers, small-scale merchants, and micro-scale ride-hailing drivers; and 2) modern informal groups (upper tier), such as contractors, content creators, artists, consultants, and gig economy workers with medium to large-scale economic activities. Concrete recommendations to increase DPLK participation among informal workers involve shifting the DPLK approach from a conventional model to an inclusive-digital model, with a focus on 1) prioritizing community-based financial literacy, 2) flexibility, and 3) inclusivity through pension digitization.